Structural studies of ferroelectrics of the boracite and KH₂PO₄ type - Hay, William John (The University of Edinburgh, 1979)
This thesis is concerned with structural studies of ferroelectric crystals, in particular the structure of CsD₂AsO₄ in its tetragonal paraelectrie phase and orthorhombic ferroelectric phase and the structures of Co₃B₇O₁₃I and Cu₃B₇7O₁₃Br in their cubic paraelectric phases. Both X-ray and neutron single-crystal diffraction techniques were used. The methods of constrained least -squares refinement and significance testing were used to determine the significance of certain structural features of interest. Details of the development of a technique for the collection of single - crystal data from an unpoled and physically unconstrained crystal in its ferroelectric phase are given. The structural studies of tetragonal CsD₂AsO₄ revealed that the D ions are disordered in double minimum potential wells. In the orthorhombic phase the D ions order onto one of their two possible sites in the tetragonal phase. The displacements of the Cs, As and O ions are related to the choice of site of the D ion on the O. . . . . O bond. The As ions move away from the O ions which the D ions have moved towards. The unusual feature of the ferroelectric transition in Cs(DₓH₁₋ₓ)₂AsO₄ suggests an inhomogeneous mixing of the hydrogen and deuterium concentration. The studies of Co₃B₇7O₁₃I and Cu₃B₇7O₁₃Br show that it is not necessary to postulate disorder to explain the crystal structures of these boracites in their cubic phase.